2011
DOI: 10.1200/jco.2011.35.1494
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Deprivation Therapy and Cardiovascular Risk

Abstract: A B S T R A C T PurposeThe potential association between androgen deprivation therapy (ADT) and cardiovascular mortality (CVM) remains controversial. This study assessed mortality outcomes in a large national registry to further elucidate the association between treatment selection and cause of mortality. Patients and MethodsA total of 7,248 men in the CaPSURE registry were analyzed. Treatment was categorized as local only, primary ADT monotherapy, local treatment plus ADT, and watchful waiting/active surveill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 27 publications
(6 reference statements)
1
57
1
6
Order By: Relevance
“…age or co-morbidity, might be contributing to CV risk. These data were also analyzed using propensity scoring-a measure of the patient's probability of receiving treatment (ADT), conditional on important clinical and sociodemographic covariates (21). No differences in CV mortality were noted between those who did and did not receive ADT inferring that unmeasured variables-which influence treatment decision-making but are not recorded in CaPSUREmight have confounded the association between ADT and CV mortality in many previous studies.…”
Section: Presentation 2: Confounding Factors: An Inherent Problem Whementioning
confidence: 99%
“…age or co-morbidity, might be contributing to CV risk. These data were also analyzed using propensity scoring-a measure of the patient's probability of receiving treatment (ADT), conditional on important clinical and sociodemographic covariates (21). No differences in CV mortality were noted between those who did and did not receive ADT inferring that unmeasured variables-which influence treatment decision-making but are not recorded in CaPSUREmight have confounded the association between ADT and CV mortality in many previous studies.…”
Section: Presentation 2: Confounding Factors: An Inherent Problem Whementioning
confidence: 99%
“…Based on propensitymatching algorithm, there was no significant difference in CV mortality among men who did versus who did not receive ADT. 36 A few studies have also contradicted the association of ADT with cerebrovascular disease. The first study found that men on ADT were less likely to experience a stroke than men not undergoing ADT.…”
Section: Cardio-metabolic Complications Of Adt L Collins and S Basarimentioning
confidence: 99%
“…35 Among these men, the cumulative CV mortality at 7 years was 2.6% for men not undergoing ADT, 2.1% for men with ,6 months ADT and 1.4% for men undergoing ADT for .6 months. Punnen et al 36 analyzed a total of 7248 men in the Cancer of the Prostate Strategic Urologic Research Endeavor registry to assess the relationship between ADT and CV mortality. Competing hazard survival analysis was performed for PCa-specific, CV and all-cause mortality.…”
Section: Cardio-metabolic Complications Of Adt L Collins and S Basarimentioning
confidence: 99%
“…32 Punnen et al also analyzed a total of 7248 men to assess the relationship between ADT and CV mortality and found that there was no significant difference in CV mortality among men who did vs. those who did not receive ADT. 33 Although the relationship between ADT and CVD is controversial, many authors have shown that the profound hypogonadism in patients undergoing ADT may be responsible for high CV mortality. Low testosterone levels are a risk factor for metabolic syndrome and metabolic syndrome is also a known cause of increased CV mortality.…”
Section: Adt and Hypertensionmentioning
confidence: 99%